Modern Coffee Table Inspired by Traditional Chinese Lantern - Goh Hui Yin,; Ab Hamid, Abdullah Al Rashid (Research in Management of Technology and Business, 2021)
Coffee table is common fixture of modern interiors that it is important in life. The users often encountered problems in their living room. For example, multiple remotes scattered across the coffee table, messy papers and magazine clippings cramping the style, and those stained takeout menus cannot seem to part with. The objective of this study was to identify the characteristics of a modern coffee table that apply the elements of Chinese style in designing pattern and can be store the pile of sundries, tea set and to develop a prototype of a modern coffee table in the living room. The target user was the nuclear family which was a family group consist of two parent and one or more children. The area of survey was in my hometown which was Taman Indah Jaya at Teluk Intan area. The main areas of study were research, design development, and prototype. This research was conducted using questionnaires to determine the design criteria of the coffee table. Besides that, design development required hand sketching for ideas which was thumbnail sketching, idea development, ideation, mock-up, AutoCAD technical drawing and final design. The top of the final prototype product was made by multi-plywood according to the final design. This survey was conducted 146 respondents and collected data on the design criteria of the modern coffee table from the respondents. This research would become future reference for the students who were preparing their assignment or final year project.